Upgrading biogas into syngas via bi-reforming of model biogas over ruthenium-based nano-catalysts synthesized via mechanochemical method. (26th May 2023) - Zhang, Zhige; Bi, Guican; Han, Bing; Liu, Li; Zhong, Jiawei; Xie, Jun
Abstract: The upgrading of biogas to value-added syngas via reforming of biogas is of great significance from the perspective of green carbon science. A series of Ru based nano-catalysts (Ru/MgO, Ru/La2 O2 CO3, Ru/CeO2 ) with relatively low Ru loading and high dispersion were successfully prepared by mechanochemical method, and applied in the bi-reforming of model biogas reaction. The representative catalysts were comprehensively characterized by XRD, N2 physical adsorption, ICP-OES, SEM, XPS, H2 -TPR, CO2 -TPD, HRTEM, FTIR of CO adsorption, TPSR, TG, and Raman spectroscopy, etc. Ascribed to the appropriate basicity of MgO, homogeneous Ru dispersion with ultra-small particle size, and strong interaction between Ru ultra-small nano particles and MgO support, Ru/MgO exhibit higher CO2 adsorption and activation, higher CH4 activation and dissociation, compared with Ru/La2 O2 CO3, Ru/CeO2, which facilitate the formation of active oxygen species and intermediate coke removal, thus enhance the resistance to coke deposition and sintering. At reaction conditions of T = 750 °C and weight hourly space velocity = 32, 400 mLgCat −1 h −1, 0.5Ru/MgO catalyst exhibit satisfying catalytic activity (initial CH4 /CO2 conversation rate of 87/48%) and superior stability (stable for 150 h) with negligible deactivation rates. Graphical abstract: Image 1 Highlights: A serial of Ru-based catalysts supported on MgO, La2 O2 CO3 and CeO2 were prepared by mechanochemical method. Ru/MgO show excellent catalytic performance in bi-reforming of model biogas. The small Ru NPs, basic MgO, and interaction between Ru NPs and MgO result in satisfying catalytic performance.